SHARE FUND AND EFFECTIVENESS OF DAIRY COOPERATIVES - Wasilewski, Mirosław; Chmielewska, Marzena (Acta Scientiarum Polonorum. Oeconomia, 2006)
The paper presents an analysis of relations between a level of share fund and financial situation of dairy cooperatives. The cooperatives differed from each other with share fund’s share in liabilities and share funds. The cooperatives of the highest level of share fund presented the highest level of investments as well as satisfactory current ratio. Moreover, a relatively similar share of general liabilities in the cooperatives’ financing structure was found, what threatened to lose quick liquidity. Involvement of loan fund was usually effective, since leverage remained positive most time. No essential relations between share fund’s size and return on assets and equity were found.